Patients’ perception on the professional image in medical care: reflections for medical education - Juliane Toffoli da Silva; Angélica de Fátima Marcussi; Naura Tonin Angonese; Maiara Bordignon (Revista Brasileira de Educação Médica)
ABSTRACT Introduction: Brazilian studies on non-verbal communication and its possible impact on the relationship between health professionals and patients are still incipient in the scientific literature. Most studies are from countries other than Brazil. Objective: to identify the relationship established by people between attire styles used by physicians and different professional profiles or skills as well as to understand the way they feel about certain aspects of these professionals’ appearance. Method: this is a cross-sectional study in which 160 individuals participated in a specialized public healthcare service in the state of Paraná, Brazil. Sociodemographic data and the way in which participants perceive aspects related to physicians’ appearance were collected through a structured questionnaire and analyzed using descriptive and inferential statistics. Results: the sample mainly comprised women (70%). The participants generally demonstrated a preference for attire that included white coat, with “formal with white coat”, “scrubs with white coat” and “casual with white coat” being the most recommended styles when consulted about attire to be worn by physicians. The aspects of the professional image that most generated discomfort in relation to male professionals were dirty and wrinkled clothes and Bermuda shorts. Among female physicians, participants indicated discomfort mainly with dirty and wrinkled clothes, blouses that showed the belly, shorts and short dresses. Conclusion: attire styles that included white coat were the most preferred in general, but there are results depending on specific situations that must be considered. Dirty and wrinkled attire was the aspect that caused the most discomfort for professionals of both sexes.